2021
DOI: 10.32707/ercivet.878012
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of FXID and BLAD Diseases in Holstein Crossbreed Cattles Reared in Turkey

Abstract: Özet: Bu çalışmada Türkiye'deki Holştayn melezlerinde Sığır Lökosit Bağlanma Eksikliği (BLAD) ve Faktör XI Eksikliği (FXID) kalıtsal hastalıklarına sebep olan mutant allellerin varlığının araştırılması amaçlanmıştır. Çalışmada toplam 48 baş sığır incelenmiştir. Yapılan moleküler analizlerden sonra incelenen melez sığırların birinin BLAD taşıyıcısı olduğu, FXID taşıyıcısı bireye rastlanılmadığı görülmüştür. Bu çalışma ile bu kalıtsal hastalıkların görüldüğü saf Holştayn ırkı dışında da BLAD ve FXID'ne sebep ola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
0
0
Order By: Relevance
“…Similarly, Meydan et al, (2010) investigated the BLAD, DUMPS, CVM, Bovine Citrulinaemia (BC), and FXID diseases in 350 HF cattle reared in different regions of Türkiye in which a total of 14 and 12 animals were reported to be carriers of CVM and FXID disorders, respectively. On the contrary, no CVM carriers were reported in 150 heads of HF population raised in Kayseri province of Türkiye (Kulaklı andAkyüz 2011). Karsli et al, (2011) reported a low prevalence of FXID (0.4%), while no DUMPS carriers were present in a total of 504 animals belonging to HF breed reared in different districts of Antalya province of Türkiye.…”
Section: Resultsmentioning
confidence: 98%
“…Similarly, Meydan et al, (2010) investigated the BLAD, DUMPS, CVM, Bovine Citrulinaemia (BC), and FXID diseases in 350 HF cattle reared in different regions of Türkiye in which a total of 14 and 12 animals were reported to be carriers of CVM and FXID disorders, respectively. On the contrary, no CVM carriers were reported in 150 heads of HF population raised in Kayseri province of Türkiye (Kulaklı andAkyüz 2011). Karsli et al, (2011) reported a low prevalence of FXID (0.4%), while no DUMPS carriers were present in a total of 504 animals belonging to HF breed reared in different districts of Antalya province of Türkiye.…”
Section: Resultsmentioning
confidence: 98%